A promising water-in-salt electrolyte for aqueous based electrochemical energy storage cells with a wide potential window: highly concentrated HCOOK. Issue 85 (9th October 2019) - Liu, Ting; Tang, Lujie; Luo, Haowei; Cheng, Shuang; Liu, Meilin
Abstract : Recently, water-in-salt electrolytes have been widely reported because of their ability in broadening the potential window of aqueous based energy storage devices. Abstract : Recently, water-in-salt electrolytes have been widely reported because of their ability in broadening the potential window of aqueous based energy storage devices. Herein, another eco-friendly and cost-effective electrolyte, concentrated potassium formate of 40 M HCOOK where the water-to-salt molar ratio falls to 1.38 : 1, is proposed. The electrolyte demonstrates a wide potential window of up to 4 V (−2.5 to 1.5 V vs. Ag/AgCl) with a glassy carbon electrode. Compared with a CH3 COOK based electrolyte, the HCOOK possesses lower stable negative potential and higher ionic conductivity. For an activated carbon based supecapacitive electrode, a low discharge potential of −2.4 V vs. Ag/AgCl can be achieved. Besides, a high capacity of 321 F g −1 is obtained at 5 A g −1 and it is still as high as 121 F g −1 at 20 A g −1 . Meanwhile, typical K-battery behavior is exhibited for the KTi2 (PO4 )3 anode and a reversible capacity of 15 mA h g −1 can be delivered at 0.1 A g −1 .